Універсальний датчик частоти обертання - Смолін, Юрій Олександрович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Розглянуто вимоги до сучасних датчиків частоти обертання. Виділено діапазон частоти обертання різних вузлів електромеханічних систем. Виділено, що однією з найважливіших вимог до датчиків частоти обертання, що використовуються у складі комп’ютерних контрольно-діагностичних систем, є їх універсальність. Наведено структурну схему розробленого датчика. Описано метод вимірювання швидкості обертання та конструкція датчика. При підготовці експеримента визначені: факторні рівні; взаємозв’язок факторів; фактор основної групи і фактор підгрупи; інтервали між вимірюваннями. Проведено рандомізацію значення аргументів багатофакторного експеременту. Складено план-матрицю проведення експеремента. Наведено структурну схему експерементальної установки. Обрані засоби контролю і вимірювання. Отримані експерементальні залежності максимальної відстані включення датчика від товщини сигнальної пластини для різних матеріалів цієї пластини.

The requirements for modern speed sensors are considered. The range of rotational speed of various nodes of electromechanical systems is highlighted. The parameters of the speed sensors are determined, which are most often investigated and the main stages of the multi-stage process of studying these parameters are considered. It is noted that one of the most important requirements for speed sensors used in computer control and diagnostic systems is their versatility. The block diagram of the developed sensor is given. The method of measuring the speed of rotation and the design of the sensor are described. In this case, the main attention is paid to the analog part of the sensor, i.e., to a measuring transducer containing three nodes: a primary inductive transducer, an oscillation generator, and an amplifier. Timing diagrams explaining the principle of operation of the inductive measuring transducer and all the parameters of this transducer are given. When preparing the experiment, the following were determined: factor level; correlation of factors; main group factor and subgroup factor; intervals between measurements. The randomization of the value of the arguments of a multivariate experiment was carried out. An experimental matrix has been compiled. The block diagram of the experimental setup is given. Selected controls and measurements. Experimental dependences of the maximum distance of the sensor on the thickness of the signal plate for various materials of this plate are obtained.
Universal RPM sensor
Keywords: сигнальна пластина; експерементальна установка; відстань включення датчика; signal plate; experimental setup; sensor switching distance